Rewrite using positive exponents x^-2 y over y^-5

Question

Asked 9/14/2012 9:06:54 AM

Updated 8/9/2014 5:41:19 AM

2 Answers/Comments

Heather71|Points 1705|

ihcvin|Points 185|

armywifey4310|Points 70|

johnlennons|Points 900|

Expert answered|Eusph|Points 40|

Question

Asked 9/14/2012 9:06:54 AM

Updated 8/9/2014 5:41:19 AM

2 Answers/Comments

Rating

3

(x^-2 y)/y^-5 = y^5/(x^2 y) = y^4/x^2

Added 7/3/2014 11:50:07 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/14/2014 10:48:52 AM]

0

(12x^3 + 18x^2 - 3x ) divided by 3x is 4x^2+6x-1.

(12x^3 + 18x^2 - 3x )/3x

=12x^3/3x+18x^2/3x-3x/3x

=4x^2+6x-1.

(12x^3 + 18x^2 - 3x )/3x

=12x^3/3x+18x^2/3x-3x/3x

=4x^2+6x-1.

Added 8/9/2014 5:41:19 AM

27,201,091

questions answered

There are no comments.